Co-benefits of nature-based solutions exceed the costs of implementation - Alberto González-García; Ignacio Palomo; Anna Codemo; Mirco Rodeghiero; Titouan Dubo; Améline Vallet; Sandra Lavorel (Cell Reports Sustainability)
Summary: Nature-based solutions offer multiple benefits for ecosystems and societies, supporting their inclusion in policy and practice. This study contributes to closing the gap in quantifying the multiple outcomes of nature-based solutions by assessing 83 nature-based solutions in the Alps. We assessed biodiversity co-benefits and the monetary value of four ecosystem services (heatwave mitigation, flood regulation, climate regulation, and landslide protection) provided by these nature-based solutions to their respective beneficiaries. Forest nature-based solutions showed high values for the four ecosystem services, river and wetland nature-based solutions showed high values for biodiversity, and urban nature-based solutions contributed a lower biodiversity value but were highly cost effective, benefiting a larger population. We estimated a 2.8:1 return on investment benefiting a total of 91,324 persons. We highlight the need for integrating biodiversity and multiple ecosystem services for future nature-based solutions funding and implementation, together with their role to mitigate and adapt to climate change. Science for society: Nature-based solutions are a promising strategy for mitigating and adapting to climate change, as they provide multiple benefits to society and biodiversity. However, detailed quantitative analyses of these benefits and the cost effectiveness of such initiatives are limited. In this study, we present an analysis of 83 nature-based solutions in the Alps, where we quantified heatwave mitigation, flood regulation, carbon sequestration, and landslide protection. We also assessed the number of people who benefited, the monetary value of these benefits, and the associated costs.Our results highlight the need for an integrated approach to planning nature-based solutions. Forest nature-based solutions offer a wide range of benefits, while river and wetland nature-based solutions are more beneficial for biodiversity. Urban nature-based solutions, despite their high cost effectiveness, contribute less to biodiversity but are located where people can enjoy their benefits. Overall, the analyzed solutions show a return on investment of 2.8 EUR per EUR invested.